A typology for vulnerability and agriculture in Sub-Saharan Africa - Zhang, Xiaobo; Rockmore, Marc; Chamberlin, Jordan (International Food Policy Research Institute, 2007)
This paper considers vulnerability reduction in Sub-Saharan Africa (SSA) from a more aggregated macro viewpoint. We focus on risk related to agriculture, since vulnerability and agriculture are intimately linked in SSA due to the location of the poor, their dependence on agriculture and the inherent risks of an agricultural livelihood. We argue that agricultural growth is one of the most effective means for improving permanent incomes and reducing vulnerability. However, agriculture is not homogeneous, and the inherent risks vary across countries and regions. Therefore, we also discuss appropriate investment strategies and policy instruments for different sets of risks.